Peran Pola Asuh Orang Tua dan Implikasinya terhadap Perkembangan Sosial-Emosional Anak - Kaleb Lelo; Dian Natalia Liutani (Universitas Trunojoyo Madura, 2023)
Parenting style plays a big role in aspects of children's self-development, one of which is the child's social-emotional development. This study aims to describe parenting practices and how they influence the social and emotional development of Bukit Sion PAUD children in Raeloro Village. The research method used is qualitative. There were 10 research informants consisting of 8 parents and 2 Bukit Sion PAUD teachers. The results of the study show that the role of parenting style has a major impact on the social-emotional development of children in the Bukit Sion PAUD. This can be seen when participating in learning activities at school, children have self-awareness in the form of an independent attitude in choosing activities and completing activities given by the teacher, have a sense of responsibility for themselves and others, want to share, help and assist friends who experiencing difficulties in learning activities and respecting the excellence of others in this case respecting the work of others, and having an enthusiastic attitude in completing assignments given by the teacher. The results of this study can be used as input for teachers in formulating appropriate learning methods to achieve children's social-emotional development and also become parenting guidelines for parents.